1970
DOI: 10.3126/nelta.v16i1-2.6126
|View full text |Cite
|
Sign up to set email alerts
|

Learner Perceptions and Teacher Beliefs about Learner Autonomy in Language Learning

Abstract: Learner autonomy is one of the intriguing phenomena in the field of SLA. This has become the focal point for many scholars and researchers these days. The present study was carried out to make a survey of autonomous learning activities of the Master level students, majoring in English Education, Tribhuvan University, Nepal.It also explored their perceptions on the roles of their own and their teachers' roles, and how it has been looked at from the teachers' viewpoint. Adopting a mixed methodological design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 10 publications
7
38
0
5
Order By: Relevance
“…Concerning the last research objective to explore the similarities and differences between teachers' beliefs and learners' beliefs, a few mismatches between the teachers' and the students' beliefs have emerged. The overall findings were similar to Joshi (2011), who also found that both learner perceptions and teacher beliefs were inclined towards autonomy. The general ideas tend to support a learner-centered approach and communicative methods promoting autonomous learning, as reflected in their beliefs in various areas, namely the role of good language learners, teachers, student-peers, parents and communities, students' opportunities to choose what to learn, classroom arrangements, and learning activities outside the classroom.…”
Section: Discussionsupporting
confidence: 76%
“…Concerning the last research objective to explore the similarities and differences between teachers' beliefs and learners' beliefs, a few mismatches between the teachers' and the students' beliefs have emerged. The overall findings were similar to Joshi (2011), who also found that both learner perceptions and teacher beliefs were inclined towards autonomy. The general ideas tend to support a learner-centered approach and communicative methods promoting autonomous learning, as reflected in their beliefs in various areas, namely the role of good language learners, teachers, student-peers, parents and communities, students' opportunities to choose what to learn, classroom arrangements, and learning activities outside the classroom.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, a study shows that the students' responses to learner autonomy are positive (Tally, 2014). In another study conducted by Joshi (2011), more than 80% learners are found to be aware of the goals and the process of learning English. A reason for this is probably because Language Institute has adjusted the curriculum to be student-centered in all courses and has provided more activities that promote students' learning autonomy for quite a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed that teachers believed that the most salient factors that hindered the development of learner autonomy were learner attributes and institutional factors. Along with Bullock (2010), Joshi (2011) and Yoshiyuki (2011) found that teachers had diverging views about the extent to which their learners were autonomous. Reinders and Lazaro (2011) revealed that teachers felt that students did not understand the importance of autonomy, they lacked the skills and were reluctant to learn independently.…”
Section: Teachers' Beliefs About Learner Autonomymentioning
confidence: 99%